DEVELOPMENT OF KINETIC-EQUATIONS FOR THE EXTRACTION OF COPPER BY LIX65N BASED ON INTERFACIAL REACTION-MECHANISM - LEE, HY; KIM, SG; OH, JK (ELSEVIER SCIENCE BV, 1994)
Although a number of kinetic studies on the extraction of copper with chelating reagents have been reported they contain contradictory views on the location of chelate formation in solvent extraction and on the rate-controlling steps. In the present work a kinetic study of the extraction of copper from aqueous solutions with 5-nonyl 2 hydroxy benzophenone oxime (LIX65N) was carried out. This was achieved through the development of kinetic equations based on the interfacial reaction model as well as experiments using the Lewis type cell. The overall rate of extraction was found to be dominated both by two interfacial reactions forming the copper-oxime complex and by mass transfer in the aqueous phase. The fact that diffusional or mass transfer resistance played an important role could also be supported by the occurrence of interfacial turbulence at the initial stage of extraction, in addition to the low activation energy of the rate constant. The rate of backward reaction was proportional to [H+] and [CuR(2)], respectively, and almost independent of [H(2)R(2)].
Keywords: ACID